Security-Development Nexus - Jamilu Ibrahim Mukhtar; Ahmad Salisu Abdullahi (Journal of Contemporary Sociological Issues, 2022)
The article investigates the nexus between security and development in Nigeria. To do that, the article reviewed some security challenges in Nigeria and examined how they undermine the developmental aspiration of the country. Security of life and property is tied with the fundamental human rights partly because both security and freedom are indicators of development and partly because lack of individual and group freedom is squarely implicated on their ability to do everyday life activities within the context of all social structures- political, economic, socio-cultural, and religious. The paper adopted Conflict theory and Amartya Sen’s (1999) Development as Freedom thesis to explain the nexus between security and development in Nigeria. The article finds that there are different cases of security challenges in Nigeria, such as kidnapping, terrorism, cultism, political violence, and assassination of some serving and retired political leaders, as well as religious priests. The nexus between the two concepts is practical because the absence of security in a country will not allow a country to develop. The article concludes that the developmental challenges of Nigeria can be attributed to the myriad security challenges in the country. Thus, the article recommends that policy formulations on national development should not focus only on increasing GNP and GDP of the country’s economy as a strategy for development, but should design security measures as criteria for national development. Keywords: Security, Development, Security Challenges, Security-Development Nexus